Answer:
x = 3, y = 7
or (3,7)
Step-by-step explanation:
We are given the system of equations below:
![\large{ \begin{cases} 2x - y = - 1 \\ 3x - y = 2 \end{cases}}](https://tex.z-dn.net/?f=%20%5Clarge%7B%20%5Cbegin%7Bcases%7D%202x%20-%20y%20%3D%20%20-%201%20%5C%5C%203x%20-%20y%20%3D%202%20%5Cend%7Bcases%7D%7D)
We are required to solve the system by substitution method. What we have to do is to isolate either x-term or y-term so we can use the method. I will be isolating y-term because it is faster due to having 1 as a coefficient.
By isolating y-term, just pick one of the given equations to isolate. No need to isolate the whole system. (I will be isolating y-term of the first equation.)
![\large{ \begin{cases} y= 2x + 1\\ 3x - y = 2 \end{cases}}](https://tex.z-dn.net/?f=%20%5Clarge%7B%20%5Cbegin%7Bcases%7D%20y%3D%20%202x%20%2B%201%5C%5C%203x%20-%20y%20%3D%202%20%5Cend%7Bcases%7D%7D)
Then we substitute y = 2x+1 in the second equation.
![\large{3x - (2x + 1) = 2}](https://tex.z-dn.net/?f=%20%5Clarge%7B3x%20-%20%282x%20%2B%201%29%20%3D%202%7D)
Use the distribution property.
![\large{3x - 2x - 1 = 2}](https://tex.z-dn.net/?f=%20%5Clarge%7B3x%20-%202x%20-%201%20%3D%202%7D)
Isolate x-term to solve the equation.
![\large{x = 2 + 1} \\ \large{x = 3}](https://tex.z-dn.net/?f=%20%20%5Clarge%7Bx%20%3D%202%20%2B%201%7D%20%5C%5C%20%20%5Clarge%7Bx%20%3D%203%7D)
Since we are solving a system of equations. We have to solve for both x-value and y-value to complete. We have already found x-value, but nor y-value yet. Therefore, our next step is to substitute the value of x that we solved in any given equations. It's recommended to substitute in an equation that doesn't have high coefficient value. So I will be substituting x = 3 in the first equation.
![\large{2x - y = - 1} \\ \large{2(3) - y = - 1} \\ \large{6 - y = - 1}](https://tex.z-dn.net/?f=%20%5Clarge%7B2x%20-%20y%20%3D%20%20-%201%7D%20%20%5C%5C%20%20%5Clarge%7B2%283%29%20-%20y%20%3D%20%20-%201%7D%20%5C%5C%20%20%5Clarge%7B6%20-%20y%20%3D%20%20-%201%7D)
Isolate and solve for y-term.
![\large{6 + 1 = y} \\ \large{7 = y} \\ \large{y = 7}](https://tex.z-dn.net/?f=%20%5Clarge%7B6%20%2B%201%20%3D%20y%7D%20%5C%5C%20%20%5Clarge%7B7%20%3D%20y%7D%20%5C%5C%20%20%5Clarge%7By%20%3D%207%7D)
Since we substitute x = 3 and get y = 7. We can write in ordered pairs as (3,7)
Hence, the solution is (3,7)